NLRP3 and beyond: inflammasomes as central cellular hub and emerging therapeutic target in inflammation and disease - Pinzón-Fernández, María Virginia; Saavedra-Torres, Jhan S.; López Garzón, Nelson Adolfo; Pachon-Bueno, Jessica S.; Tamayo-Giraldo, Francisco Javier; Rojas Gomez, María Camila; Arias-Intriago, Marlon; Gaibor-Pazmiño, Alice; López-Cortés, Andrés; Izquierdo-Condoy, Juan S. (Frontiers in Immunology, 2025)
The NLRP3 inflammasome is a key cytosolic sensor in the innate immune system, activated by diverse danger signals such as metabolic stress, infections, and structural cellular disruptions. Its activation leads to the maturation of IL-1β and IL-18 and induces pyroptosis through gasdermin D cleavage. Multiple regulatory mechanisms modulate NLRP3 activation, including BRCC3-mediated deubiquitination, lysine carbamylation, intracellular trafficking to the microtubule-organizing center, and endolysosomal localization via PI4P. Dysregulation of these checkpoints contributes to inflammatory, neurodegenerative, hepatic, metabolic, and infectious diseases. Beyond pathogen defense, inflammasomes influence tissue regeneration, cell death pathways, and sterile inflammation, highlighting their role as integrative immune hubs. Alternative inflammatory pathways involving gasdermin E and caspase-8/3 enable persistent cytokine release in the absence of gasdermin D, revealing redundant effector arms within the inflammasome network. Structural triggers such as potassium efflux and intracellular transport disruptions lower the threshold for inflammasome assembly, while hypoxic conditions link its activation to immunometabolic imbalance. Aggresome-like mechanisms further reflect a convergence between proteostasis and inflammation. While NLRP3 remains the most extensively characterized, other inflammasomes—including NLRP1 in epithelial ribotoxic stress, CARD8 in HIV-1 protease sensing, and AIM2/IFI16 in viral and DNA sensing—highlight the diversity of inflammasome signaling in tissue- and pathogen-specific contexts. Small molecules such as MCC950, thiolutin, HDAC6 inhibitors, and CuET have demonstrated efficacy in preclinical models by selectively modulating inflammasome components or their regulatory pathways. Novel strategies such as carbamylation-mediated suppression and disruption of endocytic dynamics offer additional therapeutic entry points. A deeper understanding of inflammasome biology is essential for advancing precision immunotherapy in inflammatory and infectious diseases.